Implementation of Video Tutorials on Creating Party Dress Designs to Improve Learning Outcomes of Phase E Students at SMKN 1 Baureno - Idris, Najwa Kanaya; Marniati, Marniati (Universitas Syiah Kuala, 2025)
This study aims to determine the application of video tutorial media on the material of designing party dresses. The quantitative descriptive method with the Classroom Action Research (CAR) approach was implemented in two cycles. The research population was all students of SMK Negeri 1 Baureno, while the research sample was 21 students of class X-1 Fashion Design. Data collection techniques used questionnaires, cognitive test results, and student psychomotor practice results. The results showed that video tutorials help students learn independently, can be repeated at any time, and present clear work steps to facilitate understanding. In addition, the use of video tutorials also increases student learning motivation and activeness because the visual presentation of the material makes the learning process more interesting and easy to follow. In conclusion, the application of video tutorial media in learning to design party dresses is effective and improves student learning outcomes.